Relationship between different lactate threshold determinations in long-distance male runners - Santos, T. M.; Gomes, P. S. (Medicine & Science in Sports & Exercise, 1998)
This study compared the determination of lactate threshold (LT) using two different exercise treadmill protocols and criteria in long distance runners. The two protocols were: 4-min at 3.5 mph at 0 degrees slope warm-up; followed by a 25 slope increase and speed increase to 5 mph; thereafter 1.1 mph increments every 2 minutes until exhaustion. 6-min at 0 degrees slope warm-up with speeds being 3 minutes at 3.5 mph and 3 minutes at half-way between 3.5 mph and the velocity of 60% VO2peak, followed by 2-min increments based on a formula. Significant differences between the two protocols were recorded for various expressions of LT and its components. Implication. When referencing and comparing lactate thresholds, not only the criteria used, but the protocol exercised needs to be similar.